(untitled) (Research, Society and Development, 2024)
The main instrument of Brazilian agricultural policy is rural credit, and intrinsic characteristics of agricultural production, such as the temporal mismatch between expenses and revenues, make working capital essential for sustaining the activity. The amount made available through the 2021/2022 Agricultural Plan was R 251.22 billion, with R 177.78 billion for operating, commercialization, and industrialization, and R 73.44 billion for investments. The objective of this study was to conduct research on rural credit to finance innovation in agricultural activities. The exploration led to the Inovagro program, where the goal was to analyze the historical evolution of the adoption of this credit modality in the southern region of Brazil, as it holds greater relevance to the program. The study is characterized as applied research with an exploratory objective, using a qualitative approach. The data collection procedure involved bibliographic research, and the data used in this study were collected from the BNDES system. They are historical data from the period 2013 to 2021, portraying information on disbursement, number of contracts, and company size. The data were organized, tabulated, and graphs were generated for analysis using Microsoft Excel. The state of Paraná presented higher values for the analyzed parameters, despite a decline in these values in 2021. The average ticket graph indicated an upward trend from the year 2017. The companies taking credit from the program are mostly micro and small, accounting for 97% participation in the program.